What Do Spatial Distortions in Patients’ Drawing After Right Brain Damage Teach Us About Space Representation in Art? - Rode, Gilles; Vallar, Giuseppe; Chabanat, Eric; Revol, Patrice; Rossetti, Yves (Frontiers in Psychology, 2018)
The right cerebral hemisphere plays a crucial rule in spatial cognition, spanning from perception of elementary features, such as location, colour, line orientation or shape to representation of different spaces (3D space, allocentric, egocentric, face, personal, peri-personal or imaginal). One important aspect of its contribution concerns the perception of space symmetry and the representation of objects and scenes, with reference to the midline or body axis. This representation results from a balance between spatial attention processes depending from the two hemispheres. Healthy participants tend to show a discrete deviation of the midline plane representation toward the left side, that is likely to result from the predominance of the activity of the right cerebral hemisphere, mainly oriented towards the contralateral side of space. The visuospatial abilities of the right hemisphere, especially for the representation of the midline plane are crucially engaged in painting and drawing processes in artists. Interestingly, the distortions created by painters of the Cubism period, characterized by an asymmetry of objects and body representations, a specific enlargement or reduction of parts of space, or even by complex distortions of 3D space are analogous to those classically reported in right-brain-damaged patients (unilateral spatial neglect, hyperschematia, constructional apraxia). Understanding the pathological mechanisms of these representation disorders provides meaningful information to apprehend visual artist creations and aesthetic perception of space.